2020
DOI: 10.1155/2020/2370253
|View full text |Cite
|
Sign up to set email alerts
|

Nrp-1 Mediated Plasmatic Ago2 Binding miR-21a-3p Internalization: A Novel Mechanism for miR-21a-3p Accumulation in Renal Tubular Epithelial Cells during Sepsis

Abstract: The mechanism underlying sepsis-associated acute kidney injury (SAKI), which is an independent risk factor for sepsis-associated death, is unclear. A previous study indicates that during sepsis miR-21a-3p accumulates in renal tubular epithelial cells (TECs) as the mediator of inflammation and mediates TEC malfunction by manipulating its metabolism. However, the specific mechanism responsible for the accumulation of miR-21a-3p in TECs during sepsis is unrevealed. In this study, a cecal ligation and puncture- (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Zhiqiang Zou et al attempted to elucidate this mechanism by analyzing septic rats and the TEC line. They showed that miR-21a-3p levels in plasma and TECs increased during sepsis by the internalization of plasmatic Ago2, which binds miR-21a-3p mediated by membrane Nrp-1 [ 259 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhiqiang Zou et al attempted to elucidate this mechanism by analyzing septic rats and the TEC line. They showed that miR-21a-3p levels in plasma and TECs increased during sepsis by the internalization of plasmatic Ago2, which binds miR-21a-3p mediated by membrane Nrp-1 [ 259 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, NRP-1 has been associated with liver pathologies [39,41] and kidney disease [42][43][44][45]50,52,53]. Urinary NRP-1 has been proposed as a biomarker for lupus nephritis [42] due to its high expression in mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other diseases that have been studied include kidney injury [42][43][44][45], autoimmune disease [46,47], and neurological disorders [48,49]. However, there is a lack of data on NRP-1 in human sepsis, despite efforts to understand its role in sepsis and its connection to kidney failure [50][51][52][53][54][55][56]. Given the involvement of NRP-1 in the immune system and regulation of vascular permeability [22,32,57,58], this study aims to investigate the role of its antagonist, sNRP-1, in critical illness and sepsis and assess its potential as a biomarker in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Nrp1 is a specific murine Treg surface marker that has been recognized as a coreceptor for a wide range of extracellular ligands, which are represented by Sema3A and Sema4A [25][26][27]34 . A series of studies have shown that Nrp1 is closely related to the suppressive capacity of Tregs, particularly Tregs in J o u r n a l P r e -p r o o f inflammatory microenvironments 21,25,35,36 promotes miR-21a-3p internalization by renal tubular epithelial cells, which aggravates SAKI 39 . In the current study, in the absence of Sema4A administration, the specific depletion of Nrp1 had no significant effect on kidney Tregs or IRI.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%